Heterosis and inbreeding depression studies in pumpkin (Cucurbita moschata Duch. ex Poir.) - V. Jansi; V. Rajasree; R. Kumar; S. Praneetha and; S. Rajeswari (Electronic Journal of Plant Breeding, 2018)
The investigation was carried out in pumpkin (Cucurbita moschata Duch. ex. Poir.) to study the heterosis and inbreeding depression for yield and yield contributing characters in three possible crosses (Odisha local x Pusa Viswas, Rajasthan local x Pusa Viswas and Ambili x Pusa Viswas) involving four parents (Odisha local, Rajasthan local, Ambili and Pusa Viswas) with four generations (P1, P2, F1and F2) in randomized block design with four replications. Relative heterosis and heterobeltiosis was found to be significant and negative for days to open first female flower, number of node at which first female flower appeared, vine length, fruit weight, fruit polar diameter, fruit equatorial diameter and sex ratio. Positive relative heterosis was observed for number of fruits per vine for most of the crosses. Hence heterosis breeding can be exploited for production of more number of fruits per vine. Significant positive heterobeltiosis was also observed for days to first female flower appearance, fruit weight, fruit equatorial diameter, fruit yield per vine and fruit yield per plot in cross II Rajathan local x Pusa Viswas. The significant inbreeding depression for all the yield characters except number of fruits per vine was observed.